Sistema de contro de inventario y su relación con la gestión de ingreso y egresos de bienes patrimoniales en la Municipalidad Provincial de Requena, 2021 - Rosales Navarro, Juan Pablo (2022)
The present study aimed to determine the relationship between the inventory control system and the management of income and expenses of heritage assets in the Provincial Municipality of Requena, 2020, therefore, a descriptive study and design has been chosen not experimental, so a sample of 21 people has been included, those who were surveyed by means of a questionnaire. Managing to conclude that the inventory control system is regular (31%), due to the fact that computer systems are sometimes used for inventory control, likewise, there are seldom technological means for inventory control, however, it always easily manages to register, modify or delete information on the assets of the system. At the same time, it is possible to determine that the management of income and expenses of heritage assets is deficient (30%), because the institution seldom handles the procedures established by the national superintendent of state assets, however, they never carry out an inventory of assets. existing physical assets, in order to verify that the quantity matches the records. Finally, it was possible to determine that inventory control is significantly related to the management of income and expenses of heritage assets in the Provincial Municipality of Requena 2020.